Spontaneous Recurrent Pneumothorax during Pregnancy Secondary to Ectopic Deciduosis - Hakimi, Ali A.; Sellers, Morgan M.; Morton, Alexander P. (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Ectopic deciduosis is a benign presence of endometrial tissue outside of the uterus during pregnancy that rarely presents with pleuropulmonary manifestations and recurrent pneumothorax.Case Description We report a 35-year-old woman at 15 weeks' gestation with a history of recurrent intrapartum right pneumothorax found to have pleural, pulmonary, and diaphragmatic lesions and a middle lobe air leak. Wedge resection of the middle lobe and mechanical pleurodesis was performed. Histopathological analysis was progesterone receptor and PAX8 positive consistent with ectopic deciduosis.Conclusion Ectopic deciduosis is a rare cause of recurrent pneumothorax in pregnancy and should be considered when evaluating these patients.
Keywords: pneumothorax; diaphragm; pathology; pleural disease; pregnancy; thoracoscopy/VATS